PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING DIPADUKAN DENGAN CAROUSEL FEEDBACK TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK KELAS IV UPT SD NEGERI 13 PINRANG - Nur Meilani; Muslimin; Wawan Krismanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low level of students' science process skills in Natural and Social Sciences (IPAS) learning in elementary schools remains an obstacle in achieving learning objectives. This condition is often caused by the use of conventional learning models that are one-way and minimal active participation of students in scientific activities such as observation, measurement, grouping, and drawing conclusions. As a result, students have not been able to develop science process skills optimally. This study aims to determine the differences in science process skills between students taught using a guided inquiry learning model combined with carousel feedback and students taught using a conventional learning model. This study used a quantitative approach with a quasi-experimental type and a posttest-only control group design. The population in this study were all fourth-grade students at UPT SD Negeri 13 Pinrang. The sample consisted of class IV.B as the experimental class and IV.C as the control class, each totaling 20 students. Data were collected through essay tests that measured six indicators of science process skills: observing, classifying, measuring, communicating, concluding, and predicting. The data analysis technique used an independent sample t-test. The statistical test results showed a significance value (2-tailed) of 0.000 < 0.05, indicating a significant difference between the two classes. Thus, the guided inquiry learning model combined with carousel feedback proved effective in improving students' science process skills.